Philosophical Problems of Verification and Falsification - Novotný, Zdeněk (Civilia, 2018)
The article deals with two important philosophical streams in 20th century - neo-positivism and critical rationatism - trying to "clear" philosophy of so called "metaphysical pseudo-problems". Logical positivism prefers verification, critical rationalism speaks rather about demarcation andfalsification. Neither of the two methods, however, is without problems.
Keywords: Carnap; Russell; Popper; metaphysics; truth; verification; falsification